Purified by Blood Honour Killings amongst Turks in the Netherlands - van Eck, Clementine (Amsterdam University Press, 2002)
Honour killings are murders that are carried out to purify tarnished honour, the honour in question being namus. Both men and women possess namus. For women and girls, namus means chastity, while for men it means having chaste female family members. Honour killing is a widely known phenomenon in Turkey, where the Hürriyet newspaper reports an average of six such killings a month. As a result of migration since the 1960s and 1970s, we also encounter it in Western Europe (the Netherlands, Belgium, Germany, France, Sweden and Denmark). This study examines in detail 20 cases of honour killing by Turks in the Netherlands. Particular attention is given to the social factors that play a role in the decision to commit a honour killing.